(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2019)
In the manufacturing industry, machining is a part of all manufacture in almost all metal products. Machining of holes is one of the most common processes in the manufacturing industries. Deep hole drilling,Â DHD is classified as a complex machining process .This study presents an optimization of machining parameters in DHD using Cuckoo Search algorithm, CS comprising feed rate (f), spindle speed (s), depth of hole (d) and Minimum Quantity Lubrication MQL, (m). The machining performance measured is roundness error, Re. The real experimentation was designed based on Design of Experiment, DoE which is two levels full factorial with an added centre point. The experimental results were used to develop the mathematical model using regression analysis that used in the optimization process. Analysis of variance (ANOVA) and Fisherâ€˜s statistical test (F-test) are used to check the significant of the model developed.Â According to the results obtained by experimental the minimum value of Re Â is 0.0222Âµm and by CS is 0.0198Âµm. For the conclusion, it was found that CS is capable of giving the minimum value of Re as it outperformed the result from the experimental.